Effect Of Mechanical Activation On The Fluxing Properties Of Gua Musang Feldspar And Granite Quarry Dust - Nordala, Phoumiphon (2013)
In the present study, mechanical activation was performed on samples of Gua Musang feldspar (GMF) and granite quarry dust (GQD). At first, GMF was milled for 10, 20 and 30 minutes, at 200, 300 and 400 rpm milling speeds. The powder obtained was then formed into pellets followed by firing at 1150, 1200 and 1250°C. From the milling and firing processes, 30 minutes was found to be the optimum time for milling. Therefore, in the milling process of GQD, 30 minutes was used at different milling speeds of200, 300 and 400 rpm. It was then fired at 1150, 1200 and 1250°C. At this stage, GQD was confirmed to be a suitable fluxing material as it can form a glassy phase and lower the firing temperature. Secondly, the process was followed by forming mixtures of GMF with ball clay (BC) and silica (SC) with a weight ratio of GMF 20 wt.%, 30 wt.% and 40 wt.%. These mixtures were fired at 1100, 1150 and 1200°C. In the final part, a mixture of GQD and BC without silica (SC) were prepared due to the high amount of silica in GQD. A weight ratio of GQD 40 wt.%, 50 wt.% and 60 wt.% were chosen.